Preparation and Electromagnetic Shielding Effectiveness of Metal Fibers/Polymer Composite. Issue 1 (January 2017) - Jianzhong, Wang; Jun, Ma; Hao, Zhi; Huiping, Tang
Abstract: Composite containing metal fibers are applied widely in the field of electromagnetic interference for its excellent electromagnetic shielding effectiveness (EMSE). In the present study, two kinds of composite, 316L fibers/epoxy resin composite and Cu fibers/epoxy resin composite, were achieved using infiltration and mechanical stirring, respectively, The EMSE of the composite was assessed. The results show that the EMSE of 316L fibers/epoxy resin composite increases gradually with the aspect ratio of fibers increasing from 200 to 1000, while it decreases quickly with that from 1000 to 3000. Furthermore, the EMSE of the composite increases gradually as the content of fibers increases from 10 wt% to 25 wt%. Additionally, for the 316L fibers/epoxy resin composite, the optimum parameters of 316L fibers are the diameter of 8 μm, the content of 25wt% and the aspect ratio of 1000, and the highest EMSE of the composite is about −78dB. For the Cu fibers/epoxy resin composite, the optimum parameters of Cu fibers are the diameter of 120 μm and the content of 2.0 wt%.